2020
DOI: 10.1080/2162402x.2020.1734268
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid attenuates CCR2-dependent tumor infiltration of monocytic myeloid-derived suppressor cells, limiting tumor progression

Abstract: Myeloid-derived suppressor cells (MDSCs) are immunosuppressive cells that promote tumor progression by inhibiting anti-tumor immunity and may be the cause of patient resistance to immune checkpoint inhibitors (ICIs). Therefore, MDSCs are a promising target for cancer immunotherapy, especially in combination with ICIs. Previous studies have shown that the anticonvulsant drug valproic acid (VPA) has additional anti-cancer and immunoregulatory activities due to its inhibition of histone deacetylases. We have prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 40 publications
3
20
0
Order By: Relevance
“…In light of the robust generation of MDSCs in the 4T1 model, we examined the effect of low-dose TSA on MDSCs trafficking/accumulation. Consistent with the previous studies [ 27 , 28 ], the percentages of MDSCs were markedly reduced amongst the tumor-infiltrating immune cells of low-dose TSA treated tumor-bearing mice compared to the control group in the tumors (Supplementary Fig. 5a ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In light of the robust generation of MDSCs in the 4T1 model, we examined the effect of low-dose TSA on MDSCs trafficking/accumulation. Consistent with the previous studies [ 27 , 28 ], the percentages of MDSCs were markedly reduced amongst the tumor-infiltrating immune cells of low-dose TSA treated tumor-bearing mice compared to the control group in the tumors (Supplementary Fig. 5a ).…”
Section: Resultssupporting
confidence: 92%
“…MDSCs also contribute to immune tolerance in the TME and consequently affect the efficacy of immunotherapies [ 41 ]. Consistent with previous studies [ 27 , 28 ], our data demonstrate that HDACi leads to a marked decrease of MDSCs within the tumors. This could be due in part to downregulation of the expression of CCR2 on monocytic (M)-MDSCs by HDACi, leading to the reduced infiltration of M-MDSCs into tumors [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…Recent research has revealed that this safe drug attenuates CCR2‐dependent infiltration of M‐MDSCs and limits tumor progression in EL4 and B16‐F10 models. [ 121 ]…”
Section: Myeloid‐derived Suppressor Cellsmentioning
confidence: 99%
“…Valproic acid also relieves the immunosuppressive effects of MDSCs on CD8 + T cells and NK cells, enhancing their activation in tumors. 146 Adjuvant epigenetic therapy using low-dose DNA methyltransferase (5-azacytidine) and histone deacetylase (Entinostat) inhibitors disrupts the premetastatic niche by downregulating CCR2 and CXCR2, thereby inhibiting MDSC recruitment and promoting their differentiation into macrophage-like cells. 5 A combination of low-dose adjuvant epigenetic therapy and CCR2 antagonists synergistically enhance disease-free and overall survival outcomes.…”
Section: Blocking the Recruitment Of Mdscs After Surgerymentioning
confidence: 99%